Aspirations of Undergraduate Students of Vocational Education Programmes: An Exploratory Study at AUD (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2023)
The flurry of initiatives pertaining to vocational education and skill development by the Government of India offers an interesting insight into the age-old debate around the aims of Higher Education. The two sides of the debate revolve around the questions of whether the aims of Higher Education is to provide a Liberal education or to provide productive skills training; whether the agenda is to develop human consciousness or, to generate human capital. The National Skill Development Agency aims to meet the skilling targets envisioned in the 12th Five Year Plan in order to realize India's Demographic dividend. One of the primary channels through which the key decision-makers hope to meet this is by hastening the spread of Vocational Education in India. Supporting this thrust are structures and provisions such as the National Skill Development Coordination Board, National Skill Development Corporation and the National Skills Qualification Framework, among many others. Given the rigour and importance attached to VocationalEducation and skill-based education in present-day India, it makes sense to find out how students enrolled in Higher Education perceive the idea of a vocational and skill-based education today. Using semi-structured interviews with Undergraduate Students andFaculty from SVS, AUD, the paper attempts to gain a better understanding of how the students enrolled in the B.Voc. Programmes at AUD perceive their Programme(s) and what they aspire from it. It explores the question of matches and gaps between theaspirations of students and the provisions of Higher Education. The findings will have implications for pedagogy, aiming to improve awareness, opportunities and participation in vocational and skill- based education.